2018
DOI: 10.1063/1.5042696
|View full text |Cite
|
Sign up to set email alerts
|

Electrically tunable localized states in sub-band of bilayer graphene nanoribbon

Abstract: Multiple sub-band transport in bilayer graphene nanoribbons (GNRs) with localized charge states has not been experimentally investigated owing to the difficulty of accessing into the upper sub-band. In this letter, we utilize current annealing to heavily p-dope graphene from a capping hydrogen-silsesquioxane layer. As a result, Fermi energy can be tuned into the upper sub-valence band with reasonably small gate voltage. Owing to the localized charge states, quantum dot-like characteristics are measured in bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Surface charge transfer doping is commonly employed for 2D materials as a nondestructive and efficient doping technique. [69][70][71] Fang et al have reported p-type and n-type doping to TMDs at contact regions using NO 2 and potassium as surface dopants, respectively. [72,73] Degenerate doping concentrations of 1.0 × 10 13 and 2.5 × 10 12 cm −2 were obtained for potassium-doped MoS 2 and WSe 2 , respectively.…”
Section: Surface-charge-transfer-doped Tmdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface charge transfer doping is commonly employed for 2D materials as a nondestructive and efficient doping technique. [69][70][71] Fang et al have reported p-type and n-type doping to TMDs at contact regions using NO 2 and potassium as surface dopants, respectively. [72,73] Degenerate doping concentrations of 1.0 × 10 13 and 2.5 × 10 12 cm −2 were obtained for potassium-doped MoS 2 and WSe 2 , respectively.…”
Section: Surface-charge-transfer-doped Tmdsmentioning
confidence: 99%
“…Surface charge transfer doping is commonly employed for 2D materials as a nondestructive and efficient doping technique. [ 69–71 ] Fang et al. have reported p‐type and n‐type doping to TMDs at contact regions using NO 2 and potassium as surface dopants, respectively.…”
Section: Flp‐related Contact Strategies For 2d Tmd Devicesmentioning
confidence: 99%
“…However, the structure with such small dimensions is inevitably subjected to the disorders originating from fabrication residues, substrate defects, and edge roughness. Subsequently, these disorders vary the spatial distribution of the chemical potential in the GNR, resulting in small unintended QDs and parasitic charged puddles . These localized states therefore smear out the anticipated single QD features.…”
mentioning
confidence: 99%
“…Normally, to efficiently generate complementary dopants from HSQ, i.e., to cleave both Si─H and Si─O bonds, a temperature much higher than 500 C is normally required. [22,23] First, we examine that the current annealing is capable to cleave Si─O bonds. Here, we perform the current annealing in an as-fabricated graphene device placed on the thermal SiO 2 substrate without HSQ capping, which is carried out by applying a large dc source-drain bias to the device.…”
Section: Resultsmentioning
confidence: 99%
“…We expect that the graphene channel can be fully p-doped with longer annealing. [23] The temporal change of doping concentration n eff can be quantitatively extracted from the transfer curves using the equation n eff ¼ C ox V cnp /e. Here, C ox is the capacitance per unit area of the 300 nm thick silicon dioxide, e is the elementary charge, and V cnp is the position of CNP.…”
Section: Resultsmentioning
confidence: 99%